Genetics Selection Evolution - Boichard, Didier; Dekkers, Jack.; Hayes, Helene; van der Werf, Julius; Calus, Mario; Faraut, Thomas; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Genetics Selection Evolution is an open access, peer-reviewed, online journal dedicated to original research on all aspects of genetics and selection in farm animal species and in other species that provide novel and/or relevant insights into the genetics of farm animals. With the vast, recent increase in the amount and spectrum of available genetic, genomic, phenomic, and other -omic data, there is an ever-increasing requirement for the collaboration and successful integration of varied results, techniques, and methods in furthering the advancement of the future of genetics to benefit farm animals and associated production systems. The journal Genetics Selection Evolution focuses on contributing to these developments by providing a high-visibility forum for the dissemination of original reports, reviews, and perspectives that will prompt new insights and discussions, as well as broaden the readers$1 (Bscientific interests. Genetics Selection Evolution publishes results from all levels of study, from the gene to the quantitative trait, from the individual to the population, the breed or the species. Contributions concerning both the biological approach, from molecular genetics to quantitative genetics, as well as the mathematical approach, from population genetics to statistics, are welcome. Specific areas of interest include but are not limited to: statistical genetics and genomics, breeding objectives, development and analysis of new phenotypes and large-scale phenotyping, analysis of whole-genome and other -omics data, genetic evaluation and prediction models, genomic and other selection and breeding strategies, use of biotechnology in animal breeding, integration of heterogeneous genomic data, applied and experimental selection, gene and QTL mapping and characterization, functional genomics, characterization and management of genetic diversity of populations, theory and mathematical models relevant to genetics of farm animal populations. Contributions must include statements on the relevance of the work to the broader readership of the journal.s
Keywords: Genetics; Evolution (Biology).; Agriculture; Genetics and Genomics; Evolutionary Biology; Agriculture